The Sulaimani Dialect of the Balochi Language: A Phonological Study - Baloch, Hamid Ali (sourcecoder, 2023)
The Sulaimani Dialect is one of the ancient dialects of the Balochi language which is spoken in Sindh, the Punjab and eastern parts of Balochistan. This dialect has also been named as ‘Eastern Dialect, Northern Dialect and Rindi Dialect’ by the British Orientalists. It’s of great importance because of the Classical Poetry from 1400AD-1700AD. It’s preserved the most ancient lexical elements, phrases, idioms and the proverbs in earliest form. With the passage of time and contact with the bordering new Indo-Aryan languages, the Sulaimani dialect has borrowed a few sounds from these languages, as well as maintained the original ancient Indo- Iranian and proto-Iranian sounds. This paper illustrates the process of phonetical change in Sulaimani dialect of the Balochi language as well as the preservation of the original sounds.